A CONFIGURAÇÃO DA EDUCAÇÃO À DISTÂNCIA NO BRASIL: A qualidade do ensino em questão - Carvalho, Rutineia de Oliveira (2009)
Distance learning has been presented by the Brazilian government, in the last years, as a viable alternative to achieve the secondary groups with a quality education. With this objective, were created guidelines established in the National Education Plan and other regulations, which address this type of modality that also has been implemented in Boa Vista, Roraima, replacing in some localities, the teaching presence. This study, in addition to discuss the distance learning in national level, according to the presented proposals and legislation in vigour, also sought to highlight its consequences in the boavistense context, exposing, from a critical view, the positive and negative effects of higher education mediated by technology information and communication.